Community Geography: Addressing Barriers in Public Participation GIS. (2nd January 2017) - Robinson, Jonnell A.; Block, Daniel; Rees, Amanda
Abstract : Early advocates of Public Participation Geographic Information Systems (PPGIS) envisioned a future in which members of the public (broadly) and members of marginalized communities (specifically) would utilize geographic information and spatial technologies to affect positive change within their communities. Yet in spite of the emergence and success of PPGIS, open source geospatial tools, and the geoweb, access barriers recognized by proponents of PPGIS in the mid-1990s persist. As a result, PPGIS facilitators continue to be instrumental in addressing access barriers to geospatial technologies among resource poor organizations and marginalized groups. 'Community geography', is a growing area of academic geography that leverages university community partnerships to facilitate access to spatial technology, data, and analysis. Experiences from community geography programmes at three universities (Chicago State University, Syracuse University, and Columbus State University) demonstrate the benefits and challenges of a facilitated model of PPGIS.